THE IMPLEMENTATION OF JIGSAW IN TEACHING ESP SPEAKING FOR ACCOUNTING DEPARTEMENT IN UNIVERSITY OF MUHAMMADIYAH LAMONGAN - Naajihah Mafuudloh (Journal of Research on Language Education, 2020)
Speaking is a part of spoken and productive skills. In oral communication, the speakers and listeners are actively involved in the message. The speakers transfer a message in the appropriate language, and listeners have to interpret the message. Brown (2004) defines speaking as a productive skill that can be directly and empirically. In teaching speaking, lecturers should have a proper technique to enhance the students to be more active in the speaking class. Therefore, teachers need some appropriate techniques face that condition. Jigsaw is one of cooperative learning method that will help the students gain the information not only by reading the materials, but also sharing and discussing with their friends. Jigsaw consists of several groups, in which every group consists of several students who have various in ability, gender, religion and race. The purpose of this study was to describe the implementation of Jigsaw, the supporting factors in Jigsaw, and the teacher’s obstacles in implementing Jigsaw. In conducting this study, the writer applied descriptive qualitative research as the research design because it described the phenomena that exist in the Jigsaw implementation. The data are collected in the form of words. The reseacher used observation and interview to gain the data. Based on the result that concluded, there were 3 important points. First, choosing material, making lesson plan, organizing Jigsaw in classroom, giving quiz, and evaluating were the steps in implementing Jigsaw for speaking class. Then supporting factors were media, professional teacher, situation surround the class, material, student’s motivation, and class management. Third, limited time and different level of student’s comprehension were the obstacles that faced by the lecturer. In conclusion, Jigsaw was recommended for teaching Speaking, because it gained the students to be more active and interactive in teaching and learning process.